Clinical and hematological сhanges in viral panleukopenia in cats - I. Kolomak (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Cat infectious diseases have become widespread due to the increase in the number of stray cats; feline viral panleukopenia is no exception. It is caused by a single-stranded DNA virus of feline parvovirus, characterized by high contagiousness, fever, damage to the gastrointestinal tract, respiratory organs, heart, general intoxication, and body dehydration. The research aimed to study the hematological indices of blood and biochemical indices of plasma in viral panleukopenia of cats. During the development of intestinal panleukopenia syndrome in animals, vomiting and diarrhea were noted. The development of inflammatory processes in the digestive organs causes pain in the abdominal cavity, due to which a specific “sitting posture” occurs. An acute course was most frequently noted, characterized by a sudden increase in temperature to 42 °C, vomiting, diarrhea, and cachexia. Studies of hematological indices of blood indicate the development of thrombocytosis, neutrophilia, monocytosis, and lymphocytosis, which corresponds to the acute course of the disease with a focal inflammatory process. Erythropenia leads to systemic disorders of the cardiovascular system, which provoke the weakening of the body, accompanied by cachexia. Studies of biochemical parameters of plasma indicate systemic disorders of organs developing in the body. Thus, an increase in total protein indices and globulin fractions indicates inflammatory processes in the body, particularly the digestive and urinary organs. In addition, one of the renal impairment indices was an increase in creatinine and urea, and an increase in glucose, total bilirubin, AST, and α-amylase indicates liver and pancreas dysfunction. In some cases, hepatitis and infectious toxicosis may develop. The study of hematological indices of blood and biochemical indices of plasma will ensure a complex picture of morphological changes that develop in the body of cats with panleukopenia. The obtained data will permit the monitoring of an animal's condition with the applied therapeutic scheme and the form of a prognosis.